Correlation between milk composition and selected blood indicators of liver function in ewes during lactation - Zvonko Antunović; Boro Mioč; Željka Klir Šalavardić; Ivan Širić; Valentino Držaić; Marija Jukić Grbavac; Josip Novoselec (Mljekarstvo)
The objective of this study was to research correlations between milk composition and selected blood indicators of liver function in ewes during lactation. The research was conducted with samples of milk and blood from Travnik Pramenka ewes (n = 99). Samples were collected in the area of western Slavonia in Croatia from lactating sheep grazing on natural pastures. Chemical composition of sheep milk was analysed as well as biochemical parameters in serum. Positive correlation between ALB: TGC, ALB: ALT, GUK: GGT, CHOL: ALT and AST: GGT was determined, while significant negative correlation was determined between GUK: ALB, GUK: TGC, GUK: ALT, ALB: GGT as well as ALT: GGT. Significant positive correlation was determined between blood and milk indicators, like ALB protein (r = 0.243), ALB: DMNF (r = 0.309) and ALB: SCC (r = 0.249), as well as negative correlation between TGC: MY (r = -0.264), ALT: protein (r = -0.258), lactose: TGC (r = -0.274) and ALT: DMNF (r = -0.234). The relations between indicators of milk composition, milk production and ewes blood indicators as well as their mutual connections indicate the justification of using the analysis of liver status indicators. Accordingly, by using these relations metabolic pathways of liver status indicators could be better monitored, which is important for practice regarding prevention of possible feeding errors and prevention of major production losses while maintaining the health of lactating sheep.